The Islamic Perspective on the Environment - Sharom, Azmi (Journal of Malaysian and Comparative Law, 2001)
This article is written on the premise that the state of the environment throughout the planet is now facing a crisis. The depleting resources of the world simply cannot support the present developmental models being practised. If we are to ensure that the planet is not reduced to a polluted husk there has to be a paradigm shift with regard to how we should continue. From the lawyers’ point of view, this shift will be reflected in effective policies and legislation, both national and international. However, any changes require an ideological foundation upon which to build. It can be argued that religious principles are one source of ideology that can be used for this purpose. This article will concentrate only on the Islamic perspective.